Analisis Korelasi Keterampilan Metakognitif dan Minat Belajar terhadap Hasil Belajar Siswa pada Materi Kesetimbangan Kimia - Andini, Lia; Azizah, Utiya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to analyze the correlation between metacognitive skills and learning interest in student learning outcomes in the sub-material equilibrium shift reaction. The method used is the descriptive correlation using test and questionnaire data collection techniques. The research subjects were 31 students of grade 11 IPA 6 at SMAN 1 Cerme in Gresik. Metacognitive skills data were obtained from metacognitive skills tests supported by MAI (Metacognitive Awareness Inventory) questionnaires, data on learning interest were obtained from questionnaires, and learning outcomes data were obtained from student learning outcomes tests. The analysis carried out is a statistical test. The tests conducted consisted of the Shapiro-Wilk normality test and hypothesis testing used multiple linear regression analysis. The result of this study shows positive and significant correlation between metacognitive skills and learning interest toward the students’ learning outcomes both in partial and simultaneously in chemical equilibrium, submaterial shift of chemical equilibrium, the effects of the independent variable are 76,6%, while other factors outside the research variables influenced the other 23.4%.